A Systematic Approach to Cloud Security Using SeDas Platform (International Journal of Engineering and Computer Science, 2017)
Cloud computing is one of the cutting-edge technologies used by most of the people.  Cloud  users  are requested  to  submit  the  personal  private  information  to  the Cloud by the Internet. When users do this, they hope that Cloud service provider (CSPs), will provide the privacy for the data. Self-destructing data mainly aims at providing user’s data privacy. All the data and decrypting key will get self-destruct after user specified time without any human intervention. Along with the privacy we can also be possible to achieve the Confidentiality and Integrity. The user data will get encrypted while uploading the file to the cloud using cryptographic algorithms. In order to provide Integrity we use MD5 or SHA algorithm to avoid modification of data. In this paper, we present a system that uses the active storage technique to achieve self- destruction of data based on the T10 OSD standard. A recovery mechanism is also provided to the legitimate users to obtain their data back by requesting to the cloud admin. A new key will be sent to the legitimate user either to the Email or to Mobile using this key he has to login to the SeDas platform to get back their data. So this approach is efficient to use and possible to achieve all the privacy preserving goals described.